The Influence Of Islamic Corporate Social Responsibility, Islamicity Performance Index, And Company Size On Sharia Banking Profitability - Gita Lindri Astuti; Endang Kartini Panggiarti; Chaidir Iswanaji (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2023)
This study aims to determine the effect of Islamic corporate social responsibility, islamicity performance index, and company size on the profitability of Islamic banking in 2016-2020. In research, the independent variable is the influence of ICSR, sharia performance index, and company size, the dependent variable is profitability. This study uses secondary data from the company's annual report for the 2016-2020 period. The research population is Islamic banking companies in 2016 to 2020. The research sample was obtained as many as 30 companies through the purposive sampling method. The data analysis technique used multiple linear regression. The adjusted R square value is 0.194 or 19.4%, while the remaining 80.6% is described by other variables besides the variables in the study. The results of the study show that (1) ICSR includes investment funding, service products, employees, social communities, and corporate governance. And only indicators of investment funding have a significant effect on profitability (2) Islamicity Performance Index has a significant effect on profitability of Islamic banking (3) Company size has no effect on profitability.